Insights in the vibrational optical activity spectra of the antibiotic vancomycin in DMSO. Issue 16 (11th April 2022) - Aerts, Roy; Bogaerts, Jonathan; Herrebout, Wouter; Johannessen, Christian
Abstract : The solution structure of the antibiotic vancomycin is studied in DMSO, allowing for a direct comparison of measurements done using Raman optical activity and vibrational circular dichroism. In this case, ROA wins! Abstract : Vibrational circular dichroism (VCD) and Raman optical activity (ROA) are two spectroscopic techniques that are sensitive towards the conformational behaviour of molecules, and are often complementary herein. In this work we pursue the determination of the conformational ensemble of the antibiotic glycopeptide vancomycin in DMSO through comparison of experimental and computational spectra, both for VCD and ROA. ROA is found to be highly suitable for the task, identifying an ensemble that strongly resembles the NMR conformation. In the case of VCD, however, a too high sensitivity of the intensities with respect to minor conformational changes hampers a reliable conformational analysis. Whence attempting to improve the match between the VCD experiment and calculations by any means – e.g., by inducing minor conformational changes or including solvent effects in the calculations – we show that there is the risk of going down the rabbit hole. In conclusion, this work contributes to the broader understanding of where, when and how VCD and ROA can be deployed as techniques for conformational analysis.